2009
DOI: 10.1242/jcs.036822
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Rap1 activity is required for differential adhesion, cell-type patterning and morphogenesis inDictyostelium

Abstract: cells do not exhibit impaired motility or chemotaxis, indicating that RapGAPB might only regulate specific roles of Rap1. Importantly, we also found that RapGAPB regulates Rap1 activity during multicellular development and is required for normal morphogenesis. First, streams of aggregating rapGAPB -cells break up as a result of decreased cell-cell adhesion. Second, rapGAPB -cells exhibit cell-autonomous defects in prestalk cell patterning. Using cell-type-specific markers, we demonstrate that RapGAPB is requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…RAP1A, and the highly related protein RAP1B (95% amino acid identity), belong to the Ras family of small GTPases, regulating various cellular processes such as cell adhesion and migration (14)(15)(16); studies in Xenopus and zebrafish have shown that rap1a and rap1b morphants exhibit similar gastrulation defects, highlighting the important role of both proteins in early development (17). RAP1 is known to exert opposing effects on the MAPK pathway (18), depending on tissue-and cell-specific context: an activating effect through BRAF (19,20) and a repressive effect through RAF1 (21).…”
Section: Resultsmentioning
confidence: 99%
“…RAP1A, and the highly related protein RAP1B (95% amino acid identity), belong to the Ras family of small GTPases, regulating various cellular processes such as cell adhesion and migration (14)(15)(16); studies in Xenopus and zebrafish have shown that rap1a and rap1b morphants exhibit similar gastrulation defects, highlighting the important role of both proteins in early development (17). RAP1 is known to exert opposing effects on the MAPK pathway (18), depending on tissue-and cell-specific context: an activating effect through BRAF (19,20) and a repressive effect through RAF1 (21).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that our So far, we have relied on multiple alleles and on published results to validate our screen results. The highest numbers of alleles were found in rapgapB and tgrB1, and we know that TgrB1 and TgrC1 interact to regulate development (Hirose et al 2015) and that rapgapB encodes a RapA GTPase regulatory protein B that regulates cell-cell and cell-substrate adhesion (Parkinson et al 2009). This knowledge and the availability of molecular tools allowed us to perform direct causality tests of these mutations.…”
Section: Multiple Alleles Reveal 13 Suppressors Of the Tgrb1-c1 Mismamentioning
confidence: 99%
“…For example, myosin heavy chain deficient D. discoideum cells do not form fruiting bodies but stop already at the mound stage, an early stage of development. Mutants in which the activation of the small GTPase Rap which regulates actin assembly at the posterior pole during chemotaxis, is altered have a cell adhesion defect during aggregation and a cell patterning defect in the post aggregation stage [34,40].…”
Section: Discussionmentioning
confidence: 99%